The Pengaruh Pembelajaran Berdiferensiasi Terhadap Motivasi Belajar dan Hasil Belajar Siswa Pada Materi Larutan Penyangga - Dwie Annisa; Nanda Saridewi; Rizqy Nur Solihat (Journal of Chemistry Sciences and Education, 2025)
This research was conducted due to the low motivation of students in learning chemistry materials caused by learning methods that are not in accordance with their needs. Therefore, a differentiated learning approach is needed that can meet students' learning needs. The purpose of this research was to examine the effect of differentiated learning with the help of PBL model on students' motivation and learning outcomes on buffer solution material. Researchers used pre-experiment method with one group pretest-posttest design and quantitative approach. The research sample used 34 students of class XI SMA Negeri 10 Depok in the even semester of the 2023/2024 academic year, which was selected through purposive sampling. Data was collected through a questionnaire that included 20 statements for learning motivation and formative scores for learning outcomes. The results of hypothesis testing using the Paired Sample T-test showed a Sig. (2-tailed) of 0.000, which means H0 is rejected and H1 is accepted. Based on the test results, it can be concluded that differentiated learning with the help of PBL models has a significant effect on student motivation and learning outcomes.